2011
DOI: 10.1155/2011/715251
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Studies with Umbilical Cord Mesenchymal Stromal Cells in Different Animal Models for Muscular Dystrophy

Abstract: Umbilical cord mesenchymal stromal cells (MSC) have been widely investigated for cell-based therapy studies as an alternative source to bone marrow transplantation. Umbilical cord tissue is a rich source of MSCs with potential to derivate at least muscle, cartilage, fat, and bone cells in vitro. The possibility to replace the defective muscle cells using cell therapy is a promising approach for the treatment of progressive muscular dystrophies (PMDs), independently of the specific gene mutation. Therefore, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 51 publications
3
26
0
10
Order By: Relevance
“…Functional benefit was observed in both SJL/J and Lama2 dy-2J mice. Despite this, neither human nor canine ucMSCs expressed muscle proteins [38][39][40][41], indicating that ucMSCs lack myogenic potential in vivo in animal models for muscular dystrophy. However, forced expression of MyoD in ucMSCs enhanced skeletal muscle differentiation in vitro [42] and might also be useful to stimulate their myogenic differentiation in vivo, because this approach has been used to improve skeletal muscle differentiation of MSCs from synovium and orthopedic surgery remnants in vitro and in vivo [43,44].…”
Section: Mesenchymal Stem Cells For Repair Of Dystrophic Skeletal Musclementioning
confidence: 98%
See 2 more Smart Citations
“…Functional benefit was observed in both SJL/J and Lama2 dy-2J mice. Despite this, neither human nor canine ucMSCs expressed muscle proteins [38][39][40][41], indicating that ucMSCs lack myogenic potential in vivo in animal models for muscular dystrophy. However, forced expression of MyoD in ucMSCs enhanced skeletal muscle differentiation in vitro [42] and might also be useful to stimulate their myogenic differentiation in vivo, because this approach has been used to improve skeletal muscle differentiation of MSCs from synovium and orthopedic surgery remnants in vitro and in vivo [43,44].…”
Section: Mesenchymal Stem Cells For Repair Of Dystrophic Skeletal Musclementioning
confidence: 98%
“…Human ucMSCs were transplanted systemically into Swiss Jim Lambert (SJL/J) mice [38,39] (a murine model for LGMD containing a mutation in the dysferlin gene), the laminin a2 dystrophia muscularis 2 Jackson (Lama2 dy-2J ) mice [40] (a murine model for congenital muscular dystrophy), and Golden Retriever muscular dystrophy (GRMD) dogs [39,41] (a canine model for DMD with a naturally occurring mutation in the gene encoding dystrophin). In addition, canine ucMSCs were isolated and transplanted into dog leukocyte antigen-histocompatible GRMD littermates [39].…”
Section: Mesenchymal Stem Cells For Repair Of Dystrophic Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…However, the expression of dystrophin was not detected in the animals after transplantation. Results showed that umbilical cord mesenchymal stem cells could be able to reach the animal's musculature, but would not be able to reach full differentiation in skeletal muscle cells (ZUCCONI et al, 2011). More recently, it has been reported that adipose cells derived from human stroma, when injected systemically into the dog's cephalic vein, could have the ability to penetrate, implant and express the dystrophin in the dystrophic muscle of the DGR up to 6 months after transplantation.…”
Section: Advances In Dmd Therapy Using Grmdmentioning
confidence: 99%
“…Com o recente progresso na pesquisa sobre o tratamento com as células-tronco, têm-se discutido sobre a possibilidade de regeneração tecidual ou, principalmente, da sua ação em minimizar os mecanismos de auto-perpetuação da lesão renal, tanto inflamatórios quanto imunológicos CAO et al, 2010;LIM et al, 2011;VIEIRA et al, 2011;ZUCCONI et al, 2011), sinalizando como uma nova ferramenta na terapia da DRC em cães (LIM et al, 2016 (GEDDES et al, 2013a;FOSTER, 2016;SEGEV;MELTZER;SHIPOV, 2016).…”
Section: Introductionunclassified